The Mystisim Of Bhairawa Tantra In The Myth Of Ida Ratu Gede Mas Macaling Dalem Nusa In The Balinese Cultural Tradition - Dian Saputra, I Made (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2019)
The myth of Ida Ratu Gede Mas Macaling Dalem Nusa still exists until now. The myth is so alive in the Balinese social environment that it is made to be identical with everything which is mysterious. Its existence is always connected with the practice of native healing and other growing and developing traditional spiritual practices. There are several palm-leaf manuscripts narrating the existence of Ida Ratu Gede Mas Macaling Dalem Nusa. The version narrated in one palm-leaf manuscript is different from that narrated in another. However, his existence is always connected with the existence of one small island named Nusa Penida, an island which is under his control. He is pictured as a “frightening” spirit and the myth and his existence have hypnotized the Balinese people; therefore, it is interesting to investigate the myth. The existence of the myth is described from the perspective of the mysticism of Bhairawa Tantra, which developed rapidly during its era in Bali.